Factor Analysis of High Divorce Rate in Ujung Tanjung Religious Court - sucitra, Anggun; Hakim, Abdul; Jannah, Maya (Enrichment: Journal of Multidisciplinary Research and Development, 2024)
The onset of a divorce in a family is often caused by incompatibility and differences of opinion caused by selfishness between husband and wife. In fact, marriage is to unite a difference and fill each other's shortcomings, so that the establishment of external and mental bonds that cause affection between husband and wife in the household. The impact of divorce is not only seen for the husband and wife, but the children in the family are also affected. Common causes of divorce in a family are usually more to the lack of economy, miscommunication of married couples, differences of opinion, no consequences in building a household, third person / infidelity, mental bread, excessive work activities that reduce quality time for the family, lack of attention from each partner, constant fighting, and the occurrence of domestic violence. Divorce that occurs between husband and wife can be caused by talaq by the husband and can also be caused by divorce lawsuits made by the wife. This type of research uses Juridical-Empirical law. Juridical-empirical research is legal research on the application or implementation of normative legal provisions directly on any particular legal event that occurs in Society. Results of discussion: Factors that cause high divorce rates in the jurisdiction of the Ujung Tanjung Religious Court are: a. Economic Factors, b. Third Person Factors/Infidelity, c. Domestic Violence Factors. 2. How to overcome the high divorce rate in the jurisdiction of the Ujung Tanjung Religious Court are: a. Complicating Divorce, 2. Seek to mediate with the parties.